Chloride content in goat milk as a diagnostic marker for subclinical mastitis. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The purpose of the research was to assess possible diagnostic parameters related to subclinical mastitis in goats. Materials and Methods: Individual samples of milk from goats were separated into three groups based on the chloride concentration: group I < 70 mmol/l; II group 70–85 mmol/l; III group > 85 mmol/l. The composition of milk was studied, and smears were also made. Results: When the chloride content in goat milk exceeds 85 mmol/l, the somatic cell count increases by 3.2–5.7 times in relation to milk with a chloride content below 70 mmol/l, depending on the research method used. In the second group, the indicators exceed those of the first group by 2.1–3.8 times. Compared to the second and third groups, the indicator of electrical conductivity in goats of the first group was lower by 13.1% and 31.3%, respectively. Milk from healthy goats, characterized by a chloride content of less than 70 mmol/l, shows a chlorosugar number averaging 5 (ranging from 4.1 to 5.9). In cases where chloride levels in milk exceed 85 mmol/l, the average indicator of the chlorosugar number is 7.2 (from 6.5 to 7.9). If the content of chlorides is > 85 mmol/l, a positive result of the settling test with goat’s milk is noted. Conclusion: A set of indicators such as chloride content > 85 mmol/l, the number of somatic cells >2 million/ml, chlorosugar number ≥ 7, along with confirmed results in the settling and mastidine tests—can be used as a diagnostic criterion for subclinical mastitis in goats.J. Adv. Vet. Anim. Res., 12(2): 582–588, June 2025http://doi.org/10.5455/javar.2025.l922